MacroGreen, a simple tool for detection of ADP-ribosylated proteins - Antonio Ginés García-Saura (Nature Portfolio, 2021)
García Saura et al. report a new tool, MacroGreen, to detect ADP-ribosylation by GFP fluorescence in a microplate reader, or in cells by microscopy. With superior affinity and reduced ADP-ribosyl hydrolase activity, MacroGreen is an easy to produce and suitable tool for rapid detection of ADP-ribosylated proteins in vitro without a need for specialist reagents and time-consuming methods.